Economic result for Third Sector Organizations: an exploratory study on performance assessment - Milani Filho, Marco Antonio Figueiredo (Revista Contabilidade e Controladoria - RC&C, 2009)
Considering that the Third Sector Organizations (TSO) receive resources from public and private sources, they are expected to be accountable to their stakeholders based on an assessment of use of resources and on the benefits generated to society. The lack of specific data about the performance of the organizations can cause an inappropriate allocation of scarce resources to organizations that do not represent the best option amongst the available ones. The aim of this exploratory work was to measure and to compare, under the economic perspective, the results gotten between two philanthropic organizations, in order to stimulate a conceptual debate on the criteria for assessing efficiency and on the opportunity cost in TSO. This work presents a use case of the measurement model of economic result proposed by Slomski (1996). The comparative analysis pointed out that both organizations had presented opposite economic performances to their financial results, suggesting that the simple presentation of the mandatory financial reports might not offer enough elements for the monitoring of these organizations